2017
DOI: 10.22496/atct20170122133
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Components of EEG-based Motor Imagery Classification with Quantitative Comparison

Abstract: Motor Imagery (MI) is a voluntary modulation of brain signals for specific action without real limb movement. It is essential to classify MI signal to design a brain computer interface (BCI). BCI involves a number of signal processing steps, and a lot of techniques have been developed for each step. There can be numerous combinations of these techniques at different steps that can be employed to design a BCI. This work focuses on MI-based BCI using EEG signal and reviews the existing techniques. More important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 71 publications
0
7
0
1
Order By: Relevance
“…In this study the authors proposed a novel approach but the average accuracy for the test signal is not up to the mark. Rahman et al [23] reviewed different techniques for each step of MI-based BCI and discussed detailed comparative performance analysis that can guide us to select the right technique for a particular experimental setup. This study found that important channel and feature selection are more sensitive to boost the performance of a BCI system.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the authors proposed a novel approach but the average accuracy for the test signal is not up to the mark. Rahman et al [23] reviewed different techniques for each step of MI-based BCI and discussed detailed comparative performance analysis that can guide us to select the right technique for a particular experimental setup. This study found that important channel and feature selection are more sensitive to boost the performance of a BCI system.…”
Section: Introductionmentioning
confidence: 99%
“…D k can be seen as a measure of error, the lower the better. Then, ten subjects were selected to discuss the changes in three measures under different clustering numbers (2)(3)(4)(5)(6)(7)(8)(9)(10). The results are shown in Figure 7.…”
Section: Number Of Microstate Mapsmentioning
confidence: 99%
“…The next stage is FFT. At this stage, the sample frames 𝑁 = 15.360 point in the time domain converted into the frequency domain with (5).…”
Section: 𝑁 = 𝑠𝑎𝑚𝑝𝑙𝑖𝑛𝑔 X 𝑓𝑠mentioning
confidence: 99%
“…The EEG-based system measures the bioelectrical activity of the brain and converts it into information about hand movements. The biological activity of the brain to command its limb to touch or move an object with its limb is called motor imagery [5]. EEG sensors offer a high temporal resolution, easy to transport [6], and available for monitoring the bioelectrical activity of the brain.…”
Section: Introductionmentioning
confidence: 99%